The Effect of Motivation and Knowledge on the Entrepreneurial Interest of FEBI Students at Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi - Rendy Angga Syaputra Siregar; Habriyanto Habriyanto; Ogi Saputra (Journal of Multidisciplinary Science: MIKAILALSYS, 2026)
The low level of entrepreneurial interest among university students remains a significant challenge for higher education institutions in Indonesia, as many students continue to prefer becoming job seekers rather than job creators. This study examined the partial and simultaneous effects of motivation and entrepreneurial knowledge on entrepreneurial interest among students at the Faculty of Economics and Islamic Business, Universitas Islam Negeri Sulthan Thaha Saifuddin Jambi. A quantitative approach with an associative research design was employed, involving 95 students selected through stratified random sampling. Data were collected using a Likert-scale questionnaire and analyzed through partial least squares structural equation modeling (PLS-SEM) using SmartPLS 4. The findings revealed that motivation had a positive and statistically significant effect on entrepreneurial interest, with a path coefficient of 0.638 and a T-statistic of 15.757. Entrepreneurial knowledge also had a positive and statistically significant effect on entrepreneurial interest, with a path coefficient of 0.450 and a T-statistic of 9.078. Collectively, motivation and entrepreneurial knowledge explained 80.2% of the variance in students’ entrepreneurial interest, while the remaining 19.8% was attributable to factors outside the research model. These findings demonstrate that motivation and entrepreneurial knowledge are important determinants of entrepreneurial interest. This study contributes empirical evidence to the entrepreneurship education literature and provides practical implications for higher education institutions seeking to strengthen entrepreneurship curricula and development programs that foster independent, innovative, and competitive young entrepreneurs.